The Effects of Apitherapeutic Agents on Oxidative Stress in Serum Metabolic Parameters of Hypertensive Rats Created by Nitric Oxide Synthase Inhibited - Gulhan, Mehmet Fuat; Ozdemir, Betul; Selamoglu, Zeliha; Sahna, Engin (Univ Kebangsaan Malaysia, 2021)
Hypertension is a chronic disease affecting the whole world due to its clinical effects and complications. The reduction in the release and effect of NO is one of the mechanisms of hypertension formation. Hypertension disrupts the balance between oxidant and antioxidant mechanisms. In this study, we aimed to observe biochemical changes in the blood by treatment propolis, caffeic acid phenethyl ester (CAPE) and pollen in hypertensive rats via Nco-Nitro-L-arginine methyl ester (L-NAME). Rats were divided in five groups. Rats were given L-NAME (40 mg/kg, intraperitoneally) for 14 days to make hypertensive. L-NAME and bee products were administered together with rats for 14 days, then L-NAME for 14 days. All administrated ended 28 days. There was a statistically significant (P<0.05) decrease in blood pressure (BP) in the groups in which bee products were applied. Blood pressure was lower in the pollen treated group than in the CAPE and propolis treated group (P<0.05). Paraoxanase (PON1), total antioxidant status (TAS), total oxidant status (TOS), asymmetric dimethylarginine (ADMA), nuclear factor-kappa B (NF-kappa B) levels were measured in the blood samples in all groups. In the L-NAME group; PON1, TAS, HDL, and total protein levels were found to be lower than the groups applied bee products (P<0.05). TOS, oxidative stress index (OSI), ADMA, NF-kappa B, glucose, cholesterol, LDL, friglyceride, ALT, AST, ALP levels were found to be lower in groups plus of bee products were applied compared to the group that received L-NAME (P<0.05). The results showed that oxidative stress and homeostasis can be regulated with propolis, CAPE and pollen in hypertensive rats induced L-NAME.
Keywords: Asymmetric dimethylarginine; bee products; blood; nuclear factor-kappa B; oxidative stress; paraoxanase; rat